Implementation of Informed Consent Medical Actions as Legal Protection For Health Officers at Interna Medika Karawang Clinic - Nurjana, Nunu; Arief Fakrulloh, Zudan; Redi, Ahmad (Green Publisher Indonesia, 2023)
This study aims to examine the implementation of Informed Consent which is carried out when carrying out medical medical actions, examine and discuss the occurrence of criminal acts, examine and discuss the implementation of criminal sanctions by health workers in the practice of health services at the Interna Medika Clinic Karawang. This study uses a normative legal approach, which is to see and pay attention to the rules or literature in accordance with the object of research. The problems that arise are as follows: (1). The existence of Informed Consent is very important when carrying out medical medical actions (2). The occurrence of criminal acts that may be committed by health workers in the practice of health services (3). The application of criminal sanctions for anyone in this case health workers who commit criminal acts at the time the medical action is carried out.